Abstracts (Edited by Prof. Tahir Mahmood) - Mahmood, Tahir (Pakistan Journal of Ophthalmology, 2018)
Wavefront-guided ablation: evidence for efficacy compared to traditional ablation Netto MV, Dupps JRW, Wilson SE Am J Ophthalmol 2006; 141: 360-8. Topical ocular hypotensive medication and lens opacification: evidence from the ocular hypertension treatment study Herman DC, mae o. Gordon MO, Beiser JA, Chylack LT, Lamping KA, Schein OD, Soltau JB, Kass MA Am J Ophthalmol 2006; 142: 800-10. Modulation transfer function and pupil size in multifocal and monofocal intraocular lenses in vitro Kawamorita T, Uozato H J Cataract Refract Surg 2005; 31: 2379-85. First safety study of femtosecond laser photodisruption in animal lenses: Tissue morphology and cataractogenesis Krueger RR, Kuszak J, Lubatschowski H, Myers RI, Ripken T, Heisterkamp J Cataract Refract Surg 2005; 31:2386-94. Smoking and cataract: Review of causal association Kelly SP, Thornton J, Edwards R, Sahu A, Harrison R J Cataract Refract Surg 2005; 31: 2395-2404. Correction of hyperopia by intracorneal lenses Two-year follow-up Ismail MM J Cataract Refract Surg 2006; 32:1657-60.